2007
DOI: 10.1007/s12028-007-9007-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Infection on Length of Intensive Care Unit Stay after Intracerebral Hemorrhage

Abstract: Complicating infection was an independent predictor of a prolonged ICU stay in patients with ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…It may increase under various circumstances: in response to (brain) injury, infection or inflammation; moderately elevated CRP levels have been found in smokers, under psychological stress, in atherosclerosis and diabetes and in the elderly [29,30,31]. However, we hypothesize that maximal CRP levels in the current study in the majority of cases represented systemic infection, comparable to those of Ohwaki et al[ 21] where infection was significantly associated with maximum CRP levels (p < 0.001). Interestingly, in the group of patients where no infection could be identified, median maximal CRP level was 10.1 mg/dl, while 1 patient had a CRP level of 102.8 mg/dl without other signs of infection.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It may increase under various circumstances: in response to (brain) injury, infection or inflammation; moderately elevated CRP levels have been found in smokers, under psychological stress, in atherosclerosis and diabetes and in the elderly [29,30,31]. However, we hypothesize that maximal CRP levels in the current study in the majority of cases represented systemic infection, comparable to those of Ohwaki et al[ 21] where infection was significantly associated with maximum CRP levels (p < 0.001). Interestingly, in the group of patients where no infection could be identified, median maximal CRP level was 10.1 mg/dl, while 1 patient had a CRP level of 102.8 mg/dl without other signs of infection.…”
Section: Discussionsupporting
confidence: 84%
“…Ohwaki et al[ 21] recently assessed the impact of infection on the length of ICU stay after ICH in a population of 148 patients. They report very high incidences of chest infection in 68% of patients, while 19% had urinary tract infections and 13% other infections.…”
Section: Discussionmentioning
confidence: 99%
“…Three small studies (n=62 to 148) using single-institution databases found post-stroke infection rates of 51–58%, though two studies were ICU specific. 1113 A study of 201 ICH patients from the Virtual International Stroke Trials Archive found a much lower rate of post-stroke infection (11%). 14 In multivariate analyses, post-ICH infection was associated with high NIH Stroke Scale (NIHSS) scores, age, CReactive Protein (CRP) levels, and invasive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia is common after subarachnoid hemorrhage, but its impact on outcomes is not clear [6,7]. Pneumonia (diagnosed by nonstandardized criteria) probably worsens outcomes after intraparenchymal hemorrhage [8,9]. Patients with intracranial hemorrhage may have fever [10][11][12] or leukocytosis [13] from intracranial hemorrhage or steroid use (postoperatively or for chemical meningitis), complicating the clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%